Manfaat Mata Pelajaran Ilmu Pengetahuan Sosial (IPS) Sejarah Terhadap Pembentukan Moral Peserta Didik - Sri Susanti; Wahyu Purwiyastuti; Emy _Wuryani (Universitas Pancasakti Tegal, 2018)
This research aim to study the benefit of Social Science lesson, especially the History Subject, in grade VIII of SMP Kristen Satya Wacana. The background of the problem is the concern toward nowdays situation. Indonesian people have the ability to create high national cultur that born from the idea and creation of various ethnics. In this milenial era, the junior high school students are supposed to be ready to face the technology that growing rapidly. The data of the research are obtained from mix method. The sampling technique are Saturated Sampling and Purposive Sampling. This research shows that student apply positive values that given by the History teacher. This value are: tolerance (88,5%), religious (88%), well mannered (85%), appreciating others’ opinion (84,6%), and honesty (83%). Based on the observation, researcher found that students apply the moral values very well. The History learning is beneficial in motivating the character building.